70-3x=90-43x

Simple and best practice solution for 70-3x=90-43x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 70-3x=90-43x equation:


Simplifying
70 + -3x = 90 + -43x

Solving
70 + -3x = 90 + -43x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '43x' to each side of the equation.
70 + -3x + 43x = 90 + -43x + 43x

Combine like terms: -3x + 43x = 40x
70 + 40x = 90 + -43x + 43x

Combine like terms: -43x + 43x = 0
70 + 40x = 90 + 0
70 + 40x = 90

Add '-70' to each side of the equation.
70 + -70 + 40x = 90 + -70

Combine like terms: 70 + -70 = 0
0 + 40x = 90 + -70
40x = 90 + -70

Combine like terms: 90 + -70 = 20
40x = 20

Divide each side by '40'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 3z^3*z= | | 9+3q=12+2q | | 11v-9v=4 | | 70-3x=90-11x | | (9x+12y)(9x-12y)= | | (Y-5)+x=2.5y | | 5(c-4)=6(c-5) | | log(x)-log(x+11)=-1 | | 3m-29=-44+8m | | 5(x+10)=7x-32 | | 4800000=2900000+1600x | | 3x^2+32x+20= | | -20-2x=-30 | | 6m-5=-23+9m | | -30=-84 | | 5y-4+y+30=8y+30-4y | | 3(3x+7)-7=18x+1-9x | | 2[3(X+y)-4(6x-5y)]= | | 6m-5=23+9m | | -(x-7y)-2(2y-5x)=0 | | 3(x+3)-2=3x+2 | | 3x(x^3+6)= | | 20x+25x=180 | | Y=-x+3y | | 3(b+7)=-3 | | -20-2x=30 | | 4756505=2896112+1600x | | 2(x-3)=27 | | 5-4x=4x | | 10n-40=15n+15 | | 3p-3=4(p+1)-p | | 2x+3x-5x+x=42 |

Equations solver categories